2014
DOI: 10.5489/cuaj.1263
|View full text |Cite
|
Sign up to set email alerts
|

Peristeen anal irrigation as a substitute for the MACE procedure in children who are in need of reconstructive bladder surgery

Abstract: Cite as: Can Urol Assoc J 2014;8(1-2):e12-5. http://dx.doi.org/10.5489/cuaj.1263 Published online January 14, 2014. AbstractIntroduction: We evaluate the efficacy of the Peristeen (Coloplast A/S, Kokkedal, Denmark) transanal irrigation (TAI) system, as a stool cleansing mechanism, to gain stool continence in children who need reconstructive bladder surgery and have fecal incontinence. Methods: We prospectively evaluated children with neuropathic bladder and bowel dysfunction who were intended for reconstructiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Cedar undertook a comprehensive search and selection process (Fig. 1 ) and included a further 4 observational studies of adults[ 12 15 ] and a further 10 observational studies of children [ 16 25 ]. The main outcomes in the included studies were patient-reported outcomes, which, due to the nature of the device, was appropriate.…”
Section: Cedar’s Review Of Evidencementioning
confidence: 99%
“…Cedar undertook a comprehensive search and selection process (Fig. 1 ) and included a further 4 observational studies of adults[ 12 15 ] and a further 10 observational studies of children [ 16 25 ]. The main outcomes in the included studies were patient-reported outcomes, which, due to the nature of the device, was appropriate.…”
Section: Cedar’s Review Of Evidencementioning
confidence: 99%
“…Trans anal irrigation to manage SI was used and tested previously in our institute and others[ 17 18 19 ] with good results, in an effort to avoid major surgical reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have been very promising with ranges of about 80% of those enrolled achieving social fecal continence . Alenezi et al's study looked at 18 patients with NBD who were scheduled to undergo bladder reconstruction and MACE surgeries . These children utilized Peristeen for 3 months before their planned surgery and 83% did well with the device and only underwent their bladder surgeries, holding off on their MACE …”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] Alenezi et al's study looked at 18 patients with NBD who were scheduled to undergo bladder reconstruction and MACE surgeries. 21 These children utilized Peristeen for 3 months before their planned surgery and 83% did well with the device and only underwent their bladder surgeries, holding off on their MACE. 21 The potential cost savings of Peristeen 1 versus conservative bowel management has been previous examined in a randomized trial for adult spinal cord patients over a 10 week period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation